The Importance of Knowledge Management for Improving Work Engagement of Professional Caregivers During Covid-19 Pandemic: A Study Path Analysis - Rina Anindita; Mohammad Reza Hilmy; Valentina Wibowo Fransisca (International Journal of Nursing and Health Services (IJNHS), 2021)
Introduction: Work engagement or employee involvement is an essential concern for the sustainability of hospitals around the world, especially in the Covid-19 pandemic situation. Objective: This study aims to analyze the effect of knowledge management and competence on work engagement mediated by work motivation of health workers consisting of general practitioners and nurses at Class C Private Hospital. Method: The design of this study is a quantitative causal study with a non-probability sampling design (saturated sampling). The analysis technique used the path analysis method.. Results: This study showed that [1] There is a simultaneous effect of knowledge management and competence variables on work engagement which is mediated by work motivation (F count = 21.099 with a significance of 0.000<0.005). Conclusion: Knowledge management, competence, and work motivation are beneficial in increasing work engagement for professional care providers during the Covid-19 pandemic. Recommendation: Management should manage the competence of professional care providers, monitoring, evaluation, and the human resources management system, so the implementation of knowledge management system remain qualified Keywords: knowledge management, competence, work motivation, work engagement